Nitrification of high-strength ammonium landfill leachate for improvement of river water quality in Malaysia - Norjan Yusof (Tanjong Malim, 2019)
Nitrification of high-strength ammonium landfill leachate for improvement of river water quality in Malaysia by Norjan Yusof